CLASSIFICATION OF SWIMMING SPORTS AND THEIR TEACHING METHODOLOGY - Pulatova G. Q. (Modern American Journals, 2025)
Swimming is one of the most popular and effective forms of physical activity that combines elements of endurance, flexibility, and strength. It plays a crucial role in maintaining health, developing motor coordination, and enhancing psychological stability. The classification of swimming sports provides the foundation for organizing training processes according to the specific characteristics of each discipline. Swimming includes various types such as freestyle, breaststroke, backstroke, butterfly, and medley swimming, each requiring a different technical and physiological approach. The teaching methodology of swimming focuses on mastering these techniques systematically, ensuring safety in water, and developing the physical abilities necessary for professional or recreational performance. In sports education, a structured classification helps trainers design individualized training programs, considering the athlete’s age, physical condition, and objectives. Methodological principles such as gradual load increase, biomechanical analysis, and correction of movement errors form the scientific base of modern swimming pedagogy. This research analyzes the main types of swimming sports, their biomechanical features, and didactic principles of teaching them within the framework of sports education. The article highlights the importance of differentiated instruction, psychomotor development, and technical skill acquisition for competitive success. Furthermore, it examines how the classification of swimming methods contributes to optimizing training outcomes, promoting health, and ensuring efficient pedagogical management.